Fine structure of Mytella falcata (Bivalvia) gill filaments - David, Jose Augusto de Oliveira [UNESP]; Salaroli, Renato B.; Fontanetti, Carmem S. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Bivalve filter feeders are sessile animals that live in constant contact with water and its pollutants. Their gill is an organ highly exposed to these conditions due to its large surface and its involvement in gas exchanges and feeding. The bivalve Mytella falcata is found in estuaries of Latin America, on the Atlantic as well as the Pacific Coast. It is commonly consumed, and sometimes is the only source of protein of low-income communities. In this study, gill filaments of M. falcata were characterized using histology, histochemistry and transmission electron microscopy for future comparative studies among animals exposed to environmental pollutants. Gill filaments may be divided into abfrontal, intermediate and frontal zones. Filaments are interconnected by ciliary discs. In the center of filaments, haemocytes circulate through a haemolymph vessel internally lined by an endothelium and supported by an acellular connective tissue rich in polysaccharides and collagen. The abfrontal zone contains cuboidal cells, while the intermediate zone consists of a simple squamous epithelium. The frontal zone is composed of five columnar cell types: one absorptive, mainly characterized by the presence of pinocytic vesicles in the apical region of the cell; one secretory, rarely observed and three ciliated with abundant mitochondria. All cells lining the filament exhibit numerous microvilli and seem to absorb substances from the environment. PAS staining was observed in mucous cells in the frontal and abfrontal zones. Bromophenol blue allowed the distinction of haemocytes and detection of a glycoprotein secretion in the secretory cells of the frontal region. The characteristics of M. falcata gill filaments observed in this study were very similar to those of other bivalves, especially other Mytilidae, and are suitable for histopathological studies on the effect of water-soluble pollutants. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: histochemistry; polysaccharides; protein; collagen; transmission electron microscopy; gill morphology; mussel